Development of an in-house appd elisa for Mycobacterium avium complex (MAC) antibodies detection in zoo primates - Lekko, Yusuf Madaki; Che-Amat, Azlan; Ooi, Peck Toung; Omar, Sharina; Ramanoon, Siti Zubaidah; Mazlan, Mazlina; Abdullah Jesse, Faez Firdaus (Universiti Putra Malaysia, 2024)
In non-human primates (NHPs), Mycobacterium avium complex (MAC) species are the major source of non-tuberculous mycobacteriosis, causing tuberculous-like lesions in lymph nodes and parenchymatous organs in zoo and wildlife animals. Poor species-specific detection by serological diagnosis has negatively impacted the surveillance of MAC on non-human primates. Serum was collected from suspected twelve (n = 12) NHPs with no record of health monitoring, including gibbon (n = 5), capuchins (n = 2), siamang (n = 2), mandrill (n = 1), and orangutan (n = 2). An in-house avian purified protein derivative (aPPD) enzyme-linked immunosorbent assays (ELISA) antibody detection was developed and modified based on the established protocols. The aPPD ELISA for MAC antibodies detection at serum and Protein-G dilutions of 1:200-0.5µg/ml, respectively, detected 3/12 (25%) positive serum. At both serum and Protein-G dilutions of 1:100-0.05 and 1:300-1 µg/ml, the aPPD ELISA detected 12/12 (100%), respectively. The antibody was not detected for an in-house aPPD ELISA with serum and anti-monkey immunoglobulin G (IgG) dilutions at 1:100-0.5 and 1:300-1 µg/ml. However, 2/12 (16%) was detected using serum and anti-monkey IgG dilutions at 1:200-0.05 µg/ml. An in-house aPPD ELISA procedure for MAC antibodies detection in primates, at serum and Protein-G dilutions of 1:100-0.05 and 1:300-1 µg/ml, both have shown sensitivity and specificity of 100%, positive predictive value and negative predictive value of 100%, respectively. The serum and anti-monkey IgG have shown extremely low sensitivity and specificity. In conclusion, the performance of an in-house aPPD ELISA using three different dilutions on serum and conjugates in detecting MAC in a primate has shown that Protein-G horseradish peroxidase, as secondary conjugates were able to detect MAC antibodies.